A Health-Check of Communicative Language Teaching (CLT) in Rural Primary Schools of Bangladesh - Hoque, Mohammed Shamsul; Idrus, Rozhan M; Islam, Yousuf Mahbubul (English language teaching (Toronto), 2018)
Bangladesh ELT situation has been deteriorating for the last four decades. Regional and national projects including ELTIP and EIA proved to be futile in improving this situation, especially, in the Bangladesh rural primary schools with almost 0% properly trained English teachers to implement the current CLT curriculum. This article investigates the on-going poor health-status of CLT at randomly selected schools of northern Bangladesh through delving into the research gaps linked with the ELT practitioners' own English proficiency, their training needs, motivation and teaching skills; their perception on the instructional module; and perception of the YLs of English in Bangladesh. This enquiry uses a mixed method involving a questionnaire survey, semi-structured interview with ELT teachers, teacher trainers, head-teachers and lesson observation followed by a workshop and informal discussion with 100 participants from all ELT stake-holders to validate the findings of the earlier questionnaire survey. The findings conclude that ineffective and lack of teacher training, non-availability of English subject teacher, unproductive instructional materials, unhelpful learning environment, learners' socio-economic background, teachers' poor competence in English and knowledge of CLT methods are responsible for this deterioration. It recommends that implementation of a rigorous teacher training program for CLT to produce English subject teachers for each school, production of a pedagogically user-friendly instructional module for CPD, a culture-oriented teaching-learning environment and a program of regular guidance and supervision by CLT experts would address the gaps prevailing in the ELT (and CLT) situation at the rural primary schools of Bangladesh.